2015
DOI: 10.1371/journal.pone.0128567
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy (LLLT) in Dystrophin-Deficient Muscle Cells: Effects on Regeneration Capacity, Inflammation Response and Oxidative Stress

Abstract: The present study evaluated low-level laser therapy (LLLT) effects on some physiological pathways that may lead to muscle damage or regeneration capacity in dystrophin-deficient muscle cells of mdx mice, the experimental model of Duchenne muscular dystrophy (DMD). Primary cultures of mdx skeletal muscle cells were irradiated only one time with laser and analyzed after 24 and 48 hours. The LLLT parameter used was 830 nm wavelengths at 5 J/cm² fluence. The following groups were set up: Ctrl (untreated C57BL/10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
0
18
0
4
Order By: Relevance
“…Prevention of pathology in dystrophin deficient mice by application of different antioxidants has been recently intensively investigated and reviewed (Hnia et al 2008 ; Kim et al 2013 ; Kim and Lawler 2012 ; Messina et al 2009 ; Nakae et al 2012 ; Whitehead et al 2008 ). The favourable effects in modulating the oxidative stress were also achieved by low-level laser therapy which decreased ROS and increased activity of antioxidant enzymes such as SOD, CAT and GPX (Leal Junior et al 2010 ; Macedo et al 2015 ). Additionally, the low-intensity endurance exercise has beneficial influence on skeletal muscle of mdx mice.…”
Section: Antioxidant Enzymes In Dmdmentioning
confidence: 99%
“…Prevention of pathology in dystrophin deficient mice by application of different antioxidants has been recently intensively investigated and reviewed (Hnia et al 2008 ; Kim et al 2013 ; Kim and Lawler 2012 ; Messina et al 2009 ; Nakae et al 2012 ; Whitehead et al 2008 ). The favourable effects in modulating the oxidative stress were also achieved by low-level laser therapy which decreased ROS and increased activity of antioxidant enzymes such as SOD, CAT and GPX (Leal Junior et al 2010 ; Macedo et al 2015 ). Additionally, the low-intensity endurance exercise has beneficial influence on skeletal muscle of mdx mice.…”
Section: Antioxidant Enzymes In Dmdmentioning
confidence: 99%
“…Pires et al [73] studied tendinitis in rats after 7 and 14 days and they showed that LLLT reduced the TNF-α expression only at chronic phase. Macedo et al [74] studying dystrophic muscle cells verified that LLLT treatment reduced the TNF-α and NF-κB levels. Mantineo et al [75] utilized LLLT at five frequencies (5, 25, 50, 100, and 200 Hz) for treating inflammation induced in the gastrocnemius muscle and the treatment effects occurred for all doses with a reduction of TNF-α, IL-1β, IL-6 cytokines and inflammatory cells.…”
Section: Discussionmentioning
confidence: 96%
“…The use of LLLT increases neovascularization [65] and the expression of growth factors [66] and decreases oxidative stress, inflammation [67] and myonecrosis, activating precursor cells of myogenesis (satellite cells) [32]. Studies involving muscle regeneration of elderly rats undergoing laser therapy showed an increase in the maturation of satellite cells into myoblasts and myotubes [68].…”
Section: Discussionmentioning
confidence: 99%